Faktor-Faktor yang Mempengaruhi Customer Satisfaction dan Dampaknya terhadap Habits dan Intention to Revisit Kembali di Industri Kedai Kopi Tuku - Tomokumoro, Ceminia Tinari; Berlianto, Margaretha Pink (Universitas Bunda Mulia, 2024)
This research aims to investigate the influence of Brand Awareness, Brand Image, Perceived Service Quality, Perceived Product Quality, Physical Environment, Customer Satisfaction, and Customer Habits on Intention to Revisit. The data was obtained through a survey involving the participation of 300 respondents. The researcher utilised primary data obtained by distributing questionnaires randomly through WhatsApp, Instagram, and other social media platforms using Google Forms. The sampling technique employed was non-probability sampling. The sampling technique used in this study is non-probability sampling. The respondents for this research consist of consumers of the Toko Kopi Tuku brand from the X, millennial, and Z generations who reside in the Jabodetabek area. In this study, a variance-based structural equation modelling approach was employed using Smart PLS (Partial Least Square) version 3.2.9 software. The study’s results explored the influence of Brand Awareness, Brand Image, and Perceived Product Quality on Customer Satisfaction, except for Perceived Service Quality and Physical Environment, which did not affect Customer Satisfaction. Customer Satisfaction also influences Customer Habits and Intention to Revisit. Similarly, Customer Habits affect Intention to Revisit. This study has contributed to the research on variables influencing Customer Satisfaction, Customer Habits, and Intention to Revisit.